2014
DOI: 10.1681/asn.2013010077
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl Cyclase 6 Deficiency Ameliorates Polycystic Kidney Disease

Abstract: ABSTRACTcAMP is an important mediator of cystogenesis in polycystic kidney disease (PKD). Several adenylyl cyclase (AC) isoforms could mediate cAMP accumulation in PKD, and identification of a specific pathogenic AC isoform is of therapeutic interest. We investigated the role of AC6 in a mouse model of PKD that is homozygous for the loxP-flanked PKD1 gene and heterozygous for an aquaporin-2-Cre recombinase transgene to achieve collecting duct-specific gene targeting. Collecting duct-specific knockout of polycy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 22 publications
2
54
0
1
Order By: Relevance
“…AVP-cAMP signaling within primary cilium directly regulates cyst growth in autosomal dominant polycystic kidney disease, the most common genetic cause of kidney failure (Rieg and Kohan, 2014). In a mouse model of polycystic kidney disease, loss of AC6 markedly reduced cyst formation and renal injury (Rees et al, 2014), consistent with AC6 association with an AKAP-scaffolded complex containing polycystin-2 in primary cilium (Choi et al, 2011). The localization of AC6 in osteocyte cilia likely contributes to its role in loading-induced bone adaptation (Lee et al, 2014).…”
mentioning
confidence: 88%
“…AVP-cAMP signaling within primary cilium directly regulates cyst growth in autosomal dominant polycystic kidney disease, the most common genetic cause of kidney failure (Rieg and Kohan, 2014). In a mouse model of polycystic kidney disease, loss of AC6 markedly reduced cyst formation and renal injury (Rees et al, 2014), consistent with AC6 association with an AKAP-scaffolded complex containing polycystin-2 in primary cilium (Choi et al, 2011). The localization of AC6 in osteocyte cilia likely contributes to its role in loading-induced bone adaptation (Lee et al, 2014).…”
mentioning
confidence: 88%
“…[42][43][44][45][46] The marked amelioration of the cystic disease in collecting ductspecific Pkd1 knockout mice by a concomitant AC6 knockout provides strong support to the central role of calciuminhibitable AC6. 47 PDEs are likely important in PKD, because maximal rates of degradation by PDEs exceed by one order of magnitude those rates of synthesis by ACs and hence, control compartmentalized pools of cAMP that are likely more crucial than total intracellular cAMP. Preliminary studies, showing induction of pronephric cysts in pkd1a zebrafish morphants 48 and aggravation of the cystic disease in Pkd2 WS25/2 by depletion of Pde3a, 49 point to the importance of these PDE isoforms in PKD.…”
Section: Disruption Of Intracellular Calcium Homeostasis and Pkdmentioning
confidence: 99%
“…Resulting preclinical and clinical trials have indicated the promise of this approach. 2,[5][6][7][8][9] A recent clinical trial found that the V2 receptor antagonist, Tolvaptan, slowed disease progression over 3 years, which was indicated by a 50% reduction in total kidney volume increase and a 30% slower decline in kidney function indicated by serum creatinine. 2 Lowering cAMP levels by additional means may prove even more effective.…”
mentioning
confidence: 99%